Inovasi Pelayanan SIM Nasional Presisi (SINAR) di Polresta Samarinda - Widya Amanda Rezky; Muhammad Noor; Muhammad Hairul Saleh (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This research aims to understand and describe the innovation and implementation of the National Precision Driver’s License Service called SINAR at POLRESTA Samarinda through the innovation characteristics indicator according to Rogers (2003): Relative Advantage, Compatibility, Complexity, Trialability, and Observability. It also seeks to identify and describe the benefits of this innovations to the local community of Samarinda City. This research uses a qualitative descriptive research type. The data sources consist of primary and secondary data. The data collections techniques include library research, field research involving observation, interviews, and documentation. Data analysis techniques involve data collection, data reduction, data presentation, and drawing conclusions. The research was conducted at POLRESTA Samarinda. Based on the research findings, the SINAR innovation offers a relative advantage in terms of time, energy, cost efficiency, and meets the digital needs of the Samarinda community. This innovation is easy, fast, and economical (Compatibility), but is hindered by unstable internet connections (Complexity). Limited social media outreach reduces its dissemination effectivenee (Triability). Nonetheless, SINAR features a simple and user friendly interface (Observability).